2011
DOI: 10.1007/s10544-011-9547-1
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive poly[glycidyl methacrylate-co-poly(ethylene glycol) methacrylate] brush-based flow-through microarray immunoassay device

Abstract: Flow-through immunoassay is an attractive method for fast, inexpensive and high-throughput protein analyses. However, its practical application is limited by low sensitivity. In this work, a highly sensitive flow-through microarray immunoassay device is developed, in which a poly[glycidyl methacrylate-co-poly(ethylene glycol) methacrylate] (P(GMA-co-PEGMA)) brush as a flexible matrix is uniformly coated on a glass slide through a purge-free surface-initiated atom transfer radical polymerization (SI-ATRP) to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…28,29 Dry adhesive is also capable of multifunction integration 30 and reversible sealing. 31 Due to these advantages, dry adhesive bonding has been applied in various microuidic applications including droplet-based micro-uidics, 32 electrowetting microdevice, 33,34 chip-based electrophoresis, 35 electrochemical biosensing, 36 microarray immunoassay device, 37 and optical biochips. 38 Surface chemistry and biocompatibility is one of the critical considerations for dry adhesive bonding in microuidic applications.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Dry adhesive is also capable of multifunction integration 30 and reversible sealing. 31 Due to these advantages, dry adhesive bonding has been applied in various microuidic applications including droplet-based micro-uidics, 32 electrowetting microdevice, 33,34 chip-based electrophoresis, 35 electrochemical biosensing, 36 microarray immunoassay device, 37 and optical biochips. 38 Surface chemistry and biocompatibility is one of the critical considerations for dry adhesive bonding in microuidic applications.…”
Section: Introductionmentioning
confidence: 99%
“…The enthusiasm of the modification of PDMS will be enhanced with a bifunctional polymer brush that can reduce the hydrophobicity of PDMS while providing functional groups for covalently tethering protein without further activation or involving of chemical linkers, such as EDC/NHS and glutaraldehyde. Liu et al 26,27 have reported that poly(glycidyl methacrylate-co-poly(ethylene glycol) methacrylate (poly(GMA-copEGMA)) brush-functionalized glass surface can robustly capture target proteins and reduce nonspecific binding of unrelated biomolecules for the construction of sensitive immunoassay. The impact of poly(GMA-co-pEGMA) functionalization to cell adhesion and growth is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al have reported that poly(glycidyl methacrylate‐ co ‐poly(ethylene glycol) methacrylate (poly(GMA‐ co ‐pEGMA)) brush‐functionalized glass surface can robustly capture target proteins and reduce nonspecific binding of unrelated biomolecules for the construction of sensitive immunoassay. The impact of poly(GMA‐ co ‐pEGMA) functionalization to cell adhesion and growth is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The epoxide groups can be also used for several subsequent couplings, i.e. biofunctionalization via the attachment of amine functionalized biological molecules, such as peptides, antibodies, and DNA [7,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%